Biological rhythms of the gut and microbiota - Albert Chodowiec; Mirosław Tarasewicz; Anna Łokić; Marcin Kazberuk; Anatol Panasiuk (Gastroenterology Review)
Numerous physiological processes occurring in the digestive system are subject to circadian rhythms, which are regulated by the endogenous biological clock. The motor activity of the small intestine, large intestine, and rectum operates in a 24-hour system, with significant differences between day and night periods. It is primarily correlated with the time of meals, hormone secretion rhythms, and other activities undertaken by the organism. In recent years, numerous scientific reports have emerged about the fundamental role of circadian rhythms in the proper functioning of the gut microbiota. In addition, the microbiota and its metabolites also influence the host’s daily cycles, which affects the overall state of their organism. The aim of this review is to outline the mechanisms of action and interactions between biological rhythms, gut motility, and the functioning of the gut microbiota.